Peran Dinas Arsip dan Perpustakaan Kota Bandung dalam Mengembangkan Minat Baca Masyarakat pada Program Gerobak Baca - Wicaksono, Zaidan Aulia; Karniawati, Nia (Journal of Government Science Studies, 2024)
The aim of this research is to find out the role of the Archives and Library Service (Disarpus) in developing public interest in reading through Gerobak Baca Program. The government has a vital role in providing formal and non-formal education, one of which is by providing public libraries according to community needs in order to increase people's interest in reading in accordance with the mandate of the law. The Bandung City Government, through the Bandung City Archives and Library Service (Disarpus), has various innovative programs to increase people's interest in reading, one of these programs is Gerobak Baca Program. Gerobak Baca program has a very important role in creating a society that has high quality because it has a real impact on people's need for reading materials. Gerobak Baca program is also considered to have quite a significant impact because it is easily accessible in many sub-districts in Bandung City. The research method in this study uses a descriptive method with a literature study approach. Observations were carried out by examining a number of literature references such as books, scientific journals, news and internet references that were appropriate to the research topic.